Effectiveness of the Teaching Factory Model in Vocational Education to Improve Design Thinking among Students in the Electronics Engineering Expertise Program - Moh Faisatullah; Saiful Prayogi; Muhammad Roil Bilad (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aimed to examine the effectiveness of the Teaching Factory (TEFA) model in vocational education in improving the design thinking of students in the Electronics Engineering Expertise Program and to identify the supporting and inhibiting factors in its development. The study employed mixed methods with an explanatory sequential design. The quantitative phase applied a quasi-experimental pretest-posttest control group design involving 39 eleventh-grade students at SMK Negeri 1 Pringgabaya, consisting of 19 students in the experimental group who participated in TEFA-based learning and 20 students in the control group who participated in expository instruction. The quantitative instrument was a 30-item Likert-scale design thinking questionnaire based on six dimensions of design thinking. The data were analyzed using descriptive statistics, N-gain, paired-samples t-test, independent-samples t-test, ANOVA, ANCOVA, and effect size analysis. The qualitative phase was conducted through semi-structured interviews with seven students from the experimental group and one Electronics Engineering teacher, and the data were analyzed thematically. The results showed that the experimental group experienced a greater improvement in design thinking than the control group. The mean N-gain of the experimental group was 0.63, while that of the control group was 0.39. The tests of gain, N-gain, posttest scores, ANOVA, and ANCOVA showed significant differences with large effect sizes. Improvement also occurred across all dimensions of design thinking, particularly mindfulness to the process and impacts on others, human-centeredness, and collaboratively working with diversity. The qualitative findings showed that the development of design thinking was supported by authentic learning contexts, orientation toward user needs, collaboration, prototyping, testing, product revision, teacher guidance, and practical facilities. The main obstacles included limited time, uneven coding ability, technical constraints related to sensors and circuits, and the tendency to choose safe solutions. Therefore, TEFA was effective in improving the design thinking of Electronics Engineering students in the vocational school context.